The Balkans as Europe, 1821-1914 - Snyder, Timothy 1969-; Younger, Katherine 1988- (University of Rochester Press, 2018)
Introduction / Timothy Snyder -- Balkan initiatives to make Europe : two cases from mid-nineteenth-century Dalmatia / Dominique Kirchner Reill -- The homeland as terra incognita : geography and Bulgarian national identity, 1830s-1870s / Dessislava Lilova -- Liberation in progress : Bulgarian nationalism and political economy in a Balkan perspective, 1878-1912 / Roumiana Preshlenova -- Emigrants and countries of origin : the politics of emigration in Southeastern Europe until the First World War / Ulf Brunnbauer -- The quiet revolution : consuls and the international system in the nineteenth century / Holly Case -- The hollow crown : civil and military relations during Serbia's 'golden age,' 1903-1914 / John Paul Newman
Includes bibliographical references and index
Keywords: Geschichte 1821-1914; Politik; Nationalismus; Balkanhalbinsel; Aufsatzsammlung